PREPARING STUDENTS’ READING ABILITY FOR IR 4.0: UNDERSTANDING THEIR MOST PROBLEMATIC READING COMPREHENSION SKILLS AND THE SOLUTIONS - Manfredus Muliamarfan Mbangur; Johanes Leonardi Taloko; - Vincentia SHS (Widya Mandala Surabaya Catholic University, 2019)
The Industrial Revolution 4.0 (IR 4.0) signifying manufacturing digitalization has become a major concern around the globe. Not only does it deal with industrialists or engineers, but it also deals with teachers, and education policy makers. This new revolution requires educational institutions to prepare their students to be able to adapt themselves in this new era. English, serving as a global lingua franca, still plays an important role for all students in different majors that need to be mastered. One of the English language skills, reading, must be given sufficient attention by English teachers for their students to be able to read and comprehend English texts in their job fields in the future. This study attempts to reveal the reading comprehension mastery of the Business Administration students in a private university. It examines three series of English proficiency test (EPT) exercises and a final EPT they took as the requirements to complete their study in the university. Among the thirteen micro skills in this kind of test, the students’ most problematic skills are: answering transition questions correctly (25% correctly answered), determining the tone, purpose, or course (37%), and using context to determine meaning of difficult words (42%). Possible causes and recommendations to minimize those problems are also comprehensively presented.